The Role of Sharia Cooperatives in Batik Industry Development: A Case Study in the Batik Industry Sector of Pekalongan Regency - Adella, Desy; Istiqomah, Nur; Mufidah, Muthmainnatun; Lutfiyana, Eka; Ahmadi, Muhtar Ali; Parniati (Velocity: Journal of Sharia Finance and Banking, 2024)
This research aims to analyze the role of sharia cooperatives in the economic development of the batik industry in Pekalongan Regency, an area known as the center of the batik industry in Indonesia. Using a qualitative approach through a case study method, this research focuses on the aspects of sharia-based financing, entrepreneurship training, and market network strengthening. The results show that sharia cooperatives have a significant contribution in improving the productivity, competitiveness and sustainability of batik businesses. Islamic cooperatives provide access to usury-free financing, support sharia-based financial education, and assist businesses in preparing financial reports in accordance with accounting principles. However, Islamic cooperatives face various challenges, including limited human resources, access to capital, and a lack of public understanding of the principles of Islamic economics. This study emphasizes the importance of strategic support from the government and other stakeholders to strengthen the role of Islamic cooperatives in supporting inclusive and sustainable economic growth.